Effect of environmental factors on the germination and emergence of drunken horse grass (Achnatherum inebrians). Issue 1 (19th January 2021) - Yue, Yonghuan; Jin, Guili; Lu, Weihua; Gong, Ke; Han, Wanqiang; Liu, Wenhao; Wu, Xueer
Abstract: Drunken horse grass [ Achnatherum inebrians (Hance) Keng] is a perennial poisonous weed in western China. A comprehensive understanding of the ecological response of A. inebrians germination to environmental factors would facilitate the formulation of better management strategies for this weed. Experiments were conducted under laboratory conditions to assess the effects of various abiotic factors, including temperature, light, water, pH, and burial depth, on the germination and seedling emergence of A. inebrians . The seeds germinated at constant temperatures of 15, 20, 25, 30, and 35 C and in alternating-temperature regimes of 15/5, 20/10, 25/15, 30/20, 35/25, and 40/30 C, and the germination percentages under constant and alternating temperatures ranged from 51% to 94% and 15% to 93%, respectively. Maximum germination occurred at a constant temperature of 25 C, and germination was prevented at 45/35 C. Light did not appear to affect germination. The germination percentage of seeds was more than 75% in the pH range of 5 to 10, with the highest germination percentage at pH 6. The seeds germinated at osmotic potentials of 0 MPa to −1.0 MPa, but decreasing osmotic potential inhibited germination, with no germination at −1.2MPa. After 21 d of low osmotic stress, the seeds that did not germinate after rehydration had not lost their vitality. The seedling emergence percentage was highest (90%) when seeds were buried at 1 cm, but declined with increasing burial depth, with no emergence at 9 cm. Deep tillage may be effective in limiting the germination and emergence of this species. The results of this study provide useful information on the conditions necessary for A. inebrians germination and provide a theoretical basis for science-based prediction, prevention, and control of this species.